(untitled) - Klop, Geronda (Netherlands, 2016)
Research into manipulating methane (CH4) production as a result of enteric fermentation in ruminants currently receives global interest. Using feed additives may be a feasible strategy to mitigate CH4 as they are supplied in such amounts that the basal diet composition will not be largely affected. The latter is relevant because ruminants have the capacity to convert human inedible feedstuffs into human edible energy and protein. However, the application of CH4 mitigation feed additives may be hampered by several negative side effects including trade-offs with other environmental impacts, negative effects on animal performance, and lack of persistency of the mitigating effect. The research described in this thesis addresses both the mitigating effect of feed additives as well as its persistency. The main focus was on investigating additivity of the CH4 mitigating effect of feed additives, on the adaptation of rumen microbes to long term feeding of feed additives, and on exploring the potential of rotational feeding of additives to avoid (or reduce) microbial adaptation.
Keywords: Gia súc,Cattle; Thức ăn và cho ăn,Feeding and feeds